The Design of Advertising Media to Promote the Business of Master Pet Rattanakosin Hospital - กานนท์, วนิดา; ศะศินิล, อภิสิทธิ์; ศรีพันธ์, ชนัญญา; เทียนงาม, ลัดดา; นาคสุข, พุทธินันท์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research, entitled “The Design of Advertising Media to Promote the Business of Master Pet Rattanakosin Hospital,” aimed to: (1) design and develop appropriate advertising media for promoting the hospital’s business, and (2) examine the satisfaction of the target group toward the developed media. The sample consisted of 30 pet owners or individuals interested in the hospital’s services, selected through purposive sampling from those who had viewed the advertising media via Facebook. The research instruments included: (1) static image advertisements and video clips designed by the researcher, (2) an expert evaluation form for advertising media effectiveness, and (3) a satisfaction questionnaire.            The results indicated that the developed advertising media achieved the highest level of effectiveness (mean = 4.60, S.D. = 0.51), with communication of meaning receiving the highest rating. The overall satisfaction of the target group was at a high level (mean = 4.51, S.D. = 0.50), with the modern and attractive design of the media receiving the highest score (mean = 4.70). Therefore, the developed advertising media is effective and can be appropriately applied to promote the hospital’s business.